Improving Graphic Design Skills Based on CorelDRAW for Students of SMK Ibrahimy 1 Sukorejo - Hafidz, M. Fajar; Zaehol Fatah (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2025)
The potential of social media, pamphlets, and posters and others is greatly influenced by graphic design skills. Graphic design plays a crucial role in the creative industry. Mastery of the CorelDRAW application significantly enhances student competence, especially for those in the multimedia field. One form of this effort is carried out through training activities at SMK Ibrahimy 1 Sukorejo which aims to improve students' graphic design skills through the use of the CorelDRAW application.The training program involved intensive learning, hands-on practice, and project evaluation. A total of 30 multimedia students participated in this activity, which was conducted in four stages: Presentation session, Hands-on practice session, discussion session. The evaluation results showed that 85% of students demonstrated improvement in producing better and more aesthetic designs. This indicates a strong understanding of CorelDRAW features, particularly in mastering vectors, layout design, and object manipulation.Moreover, the training succeeded in fostering student creativity to produce innovative design works with strong appeal, which can compete in the creative industry. This community service initiative is expected to strengthen vocational competencies and better prepare students to face challenges in the global job market.